THE IMPACT OF PSYCHOLOGICAL TRAUMA ON THE LIFE OF THE MAIN CHARACTER IN THE NOVEL ELEANOR OLIPHANT IS COMPLETELY FINE BY GAIL HONEYMAN - Regina Nova Tiansyah; Henny Suharyati; Shita Dewi Ratih P (Universitas Pakuan, 2021)
This article is entitled “The Impact of Psychological Trauma on The Life of The Main Character in The Novel Eleanor Oliphant is Completely Fine by Gail Honeyman”. This study aims to determine the factors and impacts of psychological trauma on the life of the main character (Eleanor). The method used in this research is descriptive method and uses library research data analysis techniques by describing the intrinsic and extrinsic elements that are contained in the novel. The theory used is Sigmund Freud's psychoanalysis. Psychoanalytic theory is used with the aim of knowing the personality state of the main character by looking at her past history. The results of this study show that the house fire that was deliberately carried out by her biological mother had an effect on Eleanor's personality and life.Keywords : trauma; impact of trauma; main character; psychoanalysis.